Disease and Mortality in Sub-Saharan Africa, Second Edition - Jamison, Dean T.; Feacham, Richard G.; Makgoba, Malegapuru W.; Bos, Eduard R.; Baingana, Florence K.; Hofman, Karen J.; Rogo, Khama O. (Washington, DC: World Bank, 2012)
Since the publication of the first edition of "Disease and Mortality in Sub-Saharan Africa" (report no. 9784 (1991)), many new sources of health and demographic information have become available, including data on trends in HIV infection from antenatal clinic surveillance sites, the first set of African life tables from a growing number of demographic surveillance sites, injury statistics from a small number of injury mortality surveillance registers, and cancer data from cancer registers. Improved methods for estimating the incidence of several other diseases, including tuberculosis, maternal mortality, and chronic diseases, have also improved the reliability of health statistics. Verbal autopsy studies have linked with demographic surveillance sites, adding to our knowledge on changes in the cause-of-death composition in several countries. Notwithstanding these advances in health statistics, a theme that emerges from all the chapters in this volume is that too little is known about trends in the diseases and conditions included here in order to monitor and evaluate the effectiveness of programs intended to produce better health outcomes. As we get closer to the 2015 end point of the Millennium Development Goals, reaching the goals will become increasingly challenging. The continued improvement of disease surveillance and other regularly published health information remains as important a priority for African health systems as it was for the first edition.